Implikasi Konflik Sosial Terhadap Pelajar Di SMAN 6 Palu (Kasus Di Kelurahan Pengawu Dan Kelurahan Duyu Kecamatan Tatanga Kota Palu) - Wahyu Ramadhan; Suyuti (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
The aim of this research is (1) Describe the background of social conflict in Pengawu Village and Duyu Village. (2) Describe the implications of social conflict in Pengawu Village and Duyu Village for students at SMAN 6 Palu. By using a Qualitative Descriptive Method. The data analysis unit is students at SMAN 6 Palu. Sampling using Snowball sampling technique. The number of informants is 15 people. Data were collected through observation, interviews, and documentation. The data collected were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that there were four factors causing conflicts in Pengawu Village and Duyu Village, namely alcoholism, anger, generational disparity, and the economy. The implications of community conflict with students at SMAN 6 Palu are fear of going to school, moving to another school, the concentration of learning is decreasing and the interest of prospective new students at SMAN 6 Palu is decreasing.